Impact of Digital Finance on Household Service Consumption in China: A Panel Analysis of Domestic Demand Drivers - Chen, Weimin; Wang, Ruoyu Wang (Ilmu Inovasi Nusantara, 2025)
In the current new situation, China’s economic growth model has shifted, with domestic demand becoming the primary driver of economic growth, particularly for service consumption. This study examines the impact of digital finance development on household service consumption. Using data from the China Household Finance Survey (CHFS), the study constructs a digital finance index at the household level. It applies a two-way fixed effects panel model to test its impact on service consumption. The research method uses a two-way fixed effects panel model to identify the relationship between digital finance development and the increase in household service consumption. Empirical findings indicate that digital finance significantly promotes service consumption among residents. After verifying the robustness of the baseline model, several heterogeneity analyses are conducted to explore variations in the effect of digital finance based on differing demographic and economic characteristics. These findings offer important implications for economic policy development, particularly in optimizing the role of digital finance in driving domestic consumption. The study’s primary recommendation is that the government and digital financial service providers expand access to and literacy in digital finance, especially among groups with limited access. This approach is expected to strengthen the role of digital finance as a primary driver of service consumption, support sustainable economic growth, and reduce inequality in access to digital financial services within society